2004
DOI: 10.1620/tjem.202.275
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Corticosteroid Eye Drops Delays the Spontaneous Remission of Pulmonary Sarcoidosis

Abstract: Topical corticosteroid eye drops are commonly used for ocular sarcoidosis. That systemic absorption of corticosteroids by eye drops may influence the clinical course of sarcoidosis may be speculated because it has been reported that the serum concentration of corticosteroids after drop administration was dose-related. To evaluate the effects of corticosteroid eye drops on the clinical course of patients with stage I pulmonary sarcoidosis, we compared the serum levels of angiotensin converting enzyme (ACE) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Patients with ocular disease often require higher doses of immunosuppression to achieve remission, 7 and those treated with topical corticosteroids for sarcoid uveitis may be less likely to achieve spontaneous remission. 8 This suggests a possible association between chronic disease and ocular involvement. The purpose of this study was to describe sarcoidosis in the predominantly male veteran population treated at Veterans Health Administration (VHA) medical centers across the country and to examine the association of ocular involvement with mortality.…”
mentioning
confidence: 99%
“…Patients with ocular disease often require higher doses of immunosuppression to achieve remission, 7 and those treated with topical corticosteroids for sarcoid uveitis may be less likely to achieve spontaneous remission. 8 This suggests a possible association between chronic disease and ocular involvement. The purpose of this study was to describe sarcoidosis in the predominantly male veteran population treated at Veterans Health Administration (VHA) medical centers across the country and to examine the association of ocular involvement with mortality.…”
mentioning
confidence: 99%
“…The ocular involvement of our patient appeared to be well controlled for a long period of time with a topical ophthalmic steroid, despite the fact that she had concurrently received oral steroids for four months. However, it has been proposed that the long-term use of corticosteroid eye drops may delay the spontaneous remission of pulmonary sarcoidosis (8). Although it is not clear whether the topical ophthalmic steroid had an impact on the pulmonary and/or thoracic sarcoid lesions of the current patient, its clinical benefit in the overall management of sarcoidosis may require careful evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with OS whose whole-body gallium ( 67 Ga) scanning was positive, the sensitivity of serum ACE increased to 100%, and the specificity was 73% ( 38 ). The serum ACE level was significantly higher in patients with OS treated with corticosteroid eye drops for 20 months than that in non-treated group, and the enlarged lymph nodes in the chest radiograph suggested that the local corticosteroid treatment might affect the clinical course of pulmonary sarcoidosis ( 79 ). About 84%–94% cases of patients have systemic sarcoidosis, while isolated neurosarcoidosis is extremely rare, with a prevalence rate of about 1%–17%.…”
Section: Other Forms Of Sarcoidosismentioning
confidence: 99%